2015
DOI: 10.1021/acs.iecr.5b00639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rheology Properties of Oil/Water Interface on Demulsification of Crude Oil Emulsions

Abstract: Chemical demulsification is widely used in the petroleum industry to remove water from crude oil all over the world. In this work, the relationship between the rheological properties of oil/water interfacial film and demulsification of crude oil emulsions was investigated. The results showed that the elastic modulus was the critical factor for the dehydration ratio, the emulsions showed high dehydration ratio when demulsifiers reduced the elastic modulus of oil–water film to a certain extent (below 5 mN/m). Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 44 publications
2
38
1
Order By: Relevance
“…M5 showed a greater reduction in the IFT values using the W:O (50:50). These data showed the ability of the demulsifier blends to penetrate into the rigid asphaltene layer on the dispersed water or oil droplets to demulsify the dispersed phase [46]. The great reduction of IFT values in short times from 5 to 20 min showed the formation of mixed interfacial films with asphaltene at the oil-water or water-oil interfaces.…”
Section: Application Of the Prepared Ail And Ail-2 As Demulsifier Formentioning
confidence: 88%
“…M5 showed a greater reduction in the IFT values using the W:O (50:50). These data showed the ability of the demulsifier blends to penetrate into the rigid asphaltene layer on the dispersed water or oil droplets to demulsify the dispersed phase [46]. The great reduction of IFT values in short times from 5 to 20 min showed the formation of mixed interfacial films with asphaltene at the oil-water or water-oil interfaces.…”
Section: Application Of the Prepared Ail And Ail-2 As Demulsifier Formentioning
confidence: 88%
“…where C o is the magnitude of water within the origin sample without demulsifier and C d is the volume of water detached when integrating the demulsifier (Wang et al, ; Tao et al, , pp. 4851–4860).…”
Section: Methodsmentioning
confidence: 99%
“…To date, many researchers (Yang et al 2018;Adewunmi and Kamal 2019;Biniaz et al 2016) had demonstrated the demulsification mechanisms of water-in-crude-oil emulsion as well as of crude-oil-in-water emulsions (Martínez-Palou et al 2013;Tao et al 2015). The studies of both types of emulsions are in mutual understanding of the emulsion stability formation and future needs to break the emulsion.…”
Section: Demulsification Mechanismsmentioning
confidence: 99%